Solution blown polymer/biowaste derived carbon particles nanofibers: An optimization study and energy storage applications - POLAT, YUSUF (ELSEVIER, 2019)
The perspective of the abundant bio-materials and the possibility to be reused attracts attention, especially when producing carbon materials for energy storage applications. In that regard, an original electrode architecture is developed for symmetrical supercapacitor cells where peanut shell derived carbon particles are used to produce polymer/carbon fibrous electrodes. To obtain freestanding polymer/carbon electrodes, polyvinylidene fluoride (PVDF) nanofibers containing ultra-high amount of carbon nanoparticles are produced via solution blowing. Composite nanofiber production parameters such as polymer concentration, solvent ratio, and carbon concentration are optimized in order to obtain defectless fibers with the largest possible amount of carbon particles. It is found that 10wt% polymer solution, 60 wt% carbon content and 50:50 wt% DMF/acetone mixture are the optimized parameters. In the second part of the study, the produced fibrous materials are used in a symmetrical supercapacitor cell with aqueous and organic electrolytes. Aqueous supercapacitor cells with high electrode mass loading show areal capacitance up to 1120 mF cm(-2). Moreover, fibrous electrodes with increased electrical conductivity show high rate capability at high currents and high cycling stability losing only 9% of its capacity after 10,000 cycles. The cycling stability of the electrodes is even more emphasized in organic supercapacitors where the cells retain 96.4% of their capacitance. The high surface area composite nanofibers are found to exhibit high energy and power values for both aqueous and organic supercapacitors. The proposed biowaste derived composition and fibrous architecture are thought to be highly promising due to high areal capacitance and stability.
Keywords: Biowaste carbon; Composite nanofibers; Supercapacitor; DOPED POROUS CARBON; ELECTRODE MATERIAL; PERFORMANCE; SUPERCAPACITORS; BATTERIES; CAPACITOR; LITHIUM; HYBRID; GROWTH